KE ADAAN SARANA DAN PRASARANA PENDIDIKAN JASMANI DI S D SE UPTD KECAMATAN SEMARANG BARAT KOTA SEMARANG TAHUN 201 5 - Liska Sukiyandari (SOSIO DIALEKTIKA : JURNAL ILMU SOSIAL HUMANIORA, 2018)
This study aims to determine the condition of facilities and infrastructure of PhysicalEducation in SD Se UPTD West Semarang District Semarang City Year 2015.This research is a descriptive research with survey research design. The subject ofthis research is teacher Penjas Se UPTD West Semarang District Semarang City.Data were collected through questionnaires, and interviews.From the results of research and analysis of data that has been described, then ingeneral sports facilities and infrastructure that includes the main or compulsivesports branch on the subject of Physical Education in Elementary Schools UPTDWest District can be knownfor gymnastics sports state facilities and infrastructure asa whole in conditions "Lacking", athletic sports in "lacking" conditions, soccer ingood condition, volleyball sport in a "sufficient" condition and a sporting sport in"sufficient" condition.Based on the results of research and discussion it can be concluded as follows: Thecondition of gymnastics facilities and infrastructure in the condition of "less". Thestate of facilities and infrastructure of athletic sports in less condition ".Circumstances and facilities of soccer sport in good condition. The condition of thefacilities and infrastructure of volleyball sport is in "enough" condition. Thecondition of facilities and infrastructure of sporting branch of kasti is in "enough"condition. Overall for the condition of facilities and infrastructure of PhysicalEducation SD Se UPTD West Semarang District in condition "enough"Key Words:Facilities and infrastructure, Physical Education